PENGARUH KESADARAN HALAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN PADA PRODUK HALAL NETWORK INTERNATIONAL (HNI) DI TOKO HALAL MART MUARA BULIAN AGENCY CENTER ASIH - Nona Elca Dahlia.K; Mashudi Hariyanto; Raden Hebat Kurnia (JURNAL ILMIAH NUSANTARA, 2025)
The research in this thesis is motivated by consumer repurchase decisions on Halal Network International (HNI) products at the Halal Mart Muara Bulian Agency Center Asih store. This study analyzes the factors that influence consumer repurchase decisions of Halal Network International (HNI) products at the Halal Mart Muara Bulian Agency Center Asih. Using a quantitative method with a survey, this study found that halal awareness and product quality have a significant influence on repurchase decisions. These results emphasize the importance of maintaining halal and product quality to maintain consumers to continue to buy HNI products. The research method used is a quantitative method with a survey approach. The population used in this study were consumers who made repeat purchases at the Halal Mart Agency Center Asih Muara Bulian Store in 2023, namely 466 consumers.